Alternative Control of Plant Pathogen Fungi Through Ethanolic Extracts of Avocado Seeds (Persea Americana Mill.) - Miriã Cristina Pereira Fagundes; Adelson Francisco de Oliveira; Vicente Luiz de Carvalho; José Darlan Ramos; Verônica Andrade dos Santos; José Carlos Moraes Rufini (Brazilian Archives of Biology and Technology, 2018)
ABSTRACT The aim of this study was to evaluate the antifungal action of ethanolic extracts of avocado seeds, by conducting two experiments in the laboratory of plant pathology of EPAMIG SUL/Lavras, MG, Brazil, in a completely randomized design with three replicates. The first consisted of the following treatments ('Breda' 3%, 'Breda' 2%, 'Margarida' 3%, 'Margarida' 2%, Control, and Ethanol) testing its inhibitory effect on two fungal species (Colletotrichum gloeosporioides and Monilinia fructicola) and the second consisted of different concentrations of extracts (0%, 0.25%, 0.50%, 0.75%, 1.0%, 1.5%, and 2.0%) on the fungus F fructicola. The evaluations were performed at three times (7, 14, and 21 days of incubation) by measurements of the mycelial diameter using a digital caliper. The data were submitted to analysis of variance and the averages were compared by Scott-Knott test at 5% probability. The results demonstrated the positive potential of the ethanolic extracts of avocado seed on the mycelial development of fungi M. fructicola and C. gloeosporioides during the evaluated days.